Biodiversity and Analysis of Antioxidant and Antibacterial Activity of Endophytic Fungi Extracts Isolated from Mangrove Avicennia marina - Noviyanto; Widjajanti, Hary; Elfita (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Avicennia marina, a mangrove species commonly found along coastal areas, plays both ecological and pharmacological roles, with its plant parts exhibiting antioxidant and antibacterial activities. This study aimed to investigate the diversity of endophytic fungi from various organs of A. marina collected from mangrove ecosystems and to explore and analyze their antioxidant and antibacterial activities. Endophytic fungi were isolated from the roots, stems, and fruits of A. marina using PDA medium and were morphologically identified. Each fungal isolate was cultivated in PDB medium for 4 weeks under static conditions, followed by extraction to obtain concentrated extracts. Antioxidant and antibacterial activities were assessed using the DPPH method and disk diffusion assay. A total of 23 fungal isolates were obtained from the roots, stems, and fruits of A. marina. The identification results showed that the root isolates had the highest genus diversity, followed by the stem and fruit isolates. The highest distribution of antioxidant and antibacterial activities was observed in the endophytic fungal extracts from fruits, followed by those from roots and stems. Notably, the majority of the 23 endophytic fungal extracts exhibited strong antioxidant and antibacterial activities. Isolates AMF3 and AMF6showed the most potent antioxidant activity, classified as very strong, with IC50 values below 20 ug/mL. Morphological identification revealed AMF3 as Neopestalotiopsis sp. and AMF6 as Aspergillus niger. This study highlights the potential of Neopestalotiopsis sp. and Aspergillus niger endophytic fungi from A. marina fruits as sources of natural antioxidant and antibacterial compounds, offering valuable insights for biotechnological applications of mangrove-associated endophytes.